Effect of temperature on spore viability of Neonectria ditissima - Fisher, B.M.; Frijters, L.; Scheper, R.W.A. (New Zealand Plant Protection, 2015)
The fungus Neonectria ditissima causes European canker on apple and pear trees in temperate regions The thermal death point of ascospores and conidia of this pathogen is unknown In this study ascospores and conidia were exposed to six temperatures between 20C and 50C for seven time intervals between 5 min and 24 h The viability of the spore suspensions was determined by germination on slides and growth on potato dextrose agar Temperatures up to 30C did not reduce spore viability Exposure to 35C for 24 h reduced conidial and ascospore germination by 92 and 85 respectively At 40C and 45C spore viability was reduced after 5 min declining rapidly with increasing exposure times No spores germinated after 5 min at 50C This study suggests that 15 min dips in 45C water may kill surface spore contamination of budwood prior to grafting Budwoodbased validation studies are now recommended